Development and validation of PROTEUS-NODAL transient analyses capabilities for molten salt reactors. (15th September 2021) - Jaradat, Mustafa K.; Park, Hansol; Yang, Won Sik; Lee, Changho
Highlights: Development of transient analysis capabilities of PROTEUS-NODAL for MSRs. Development of variational nodal diffusion solver for cylindrical geometries. Analysis of MSFR benchmark problems and MSRE experiments. Abstract: This paper presents the PROTEUS-NODAL capabilities developed for modeling and simulation of molten salt reactors (MSRs) with flowing fuel. Steady-state and transient solvers were developed to solve the coupled neutron flux and delayed neutron precursor concentration equations for a given velocity field. A variational nodal solver for cylindrical geometries was also developed. For thermal feedback calculations, a standalone thermal-hydraulics solver for flowing fuel was implemented. Verification and validation tests were performed using the Molten Salt Fast Reactor (MSFR) benchmark and the available experimental data of the Molten Salt Reactor Experiments (MSRE). The MSFR solution of PROTEUS-NODAL agreed well with the open literature solutions for all transients. The PROTEUS-NODAL results for static and transient experiments of the MSRE were in good agreement with measured values. These results indicate that the PROTEUS-NODAL code can be used reliably for steady-state and transient analyses of fast and thermal spectrum MSRs.